Safety and efficacy profile of ozenoxacin 1% cream in pediatric patients with impetigo - Adelaide A. Hebert, MD; Theodore Rosen, MD; Núria Albareda López, BS; Ilonka Zsolt, MD, PhD; Xavier Masramon (Wolters Kluwer, 2020)
Background: Ozenoxacin is a topical antibiotic approved in the United States for treatment of impetigo in adults and children age ≥2 months. This analysis evaluated the efficacy and safety of ozenoxacin in specific pediatric age groups. Methods: Data for children aged 2 months to <18 years recruited from eight countries who had participated in phase 1 and 3 trials of ozenoxacin were extracted and analyzed by age range. Results: Across studies, 644 pediatric patients with impetigo received ozenoxacin 1% cream (n = 287) or vehicle (n = 247). One study included retapamulin 1% ointment as the internal validity control (n = 110). The clinical success rate at the end of treatment and bacterial eradication rates after 3 to 4 days of treatment and at the end of treatment were significantly higher with ozenoxacin than vehicle (all p < .0001). The clinical and microbiologic success rates were higher with ozenoxacin than vehicle in the age groups of 0.5 to <2 years, 2 to <6 years, 6 to <12 years, and 12 to <18 years and were comparable to vehicle in the 2 to <6 months age group, although patient numbers were low (≤5 per treatment arm). No safety concerns with ozenoxacin were identified. Of the 362 plasma samples derived from 38 patients, four slightly exceeded the lower limit of quantification, indicating negligible systemic absorption. Conclusion: The results of this analysis suggest that ozenoxacin 1% cream is an effective and safe treatment for impetigo in pediatric patients aged 2 months to <18 years. Keywords: Ozenoxacin, Impetigo, Topical, Pediatrics, Antibiotic, Safety